IMPLEMENTING PROBLEM-BASED LEARNING IN LITERACY-ORIENTED CLASSROOMS TO ENHANCE STUDENTS' CRITICAL READING AND WRITING ENGAGEMENT - Jimylton Dethan; Treesly Yumiardi Normin Adoe; Nattapong Srisuk (Sensei International Journal of Education and Linguistic, 2025)
In the literacy-oriented classroom the students are not only asked to read but also to think critically about what they read. However, in reality many students only read to answer the questions. Problem-Based Learning is one of the models that can be used to solve this problem. This study discusses the implementation of Problem-Based Learning in literacy-oriented classrooms. The study used a mixed-method design with an experimental class and a control class. The data were collected through a literacy test, observation, interview, and student journal. The result shows that the literacy performance of the experimental class is better and the students become more active in discussion. Therefore, Problem-Based Learning is good to be applied in literacy learning.